Apparent permeability model for gas transport through micropores and microfractures in shale reservoirs. (1st February 2021) - Gao, Qi; Han, Songcai; Cheng, Yuanfang; Li, Yang; Yan, Chuanliang; Han, Zhongying
Highlights: New apparent permeability model to describe gas transport in shale matrix is proposed. Effects of poromechanics, flow regimes, gas sorption and fractal distribution of microstructures on gas flow are considered. Gas flow behaviours in micropores and microfractures are analyzed and compared. Results provide new insights for understanding gas transport behaviours in shale reservoirs. Abstract: With the rapid development of horizontal well drilling and hydraulic fracturing techniques, shale gas has become a major source of energy in recent years. However, accurately characterizing the gas flow behaviour and predicting the permeability evolution in shale matrix is still a challenge at present due to the existence of complex microstructures and volatile reservoir conditions. In this paper, an improved apparent permeability model is developed to analyze real gas transport through micropores and microfractures in shale formation. This new model is able to consider the combined effects of poromechanics, non-Darcy flow, gas sorption and fractal distribution of microstructures on gas apparent permeability. The results indicate that (1) microfracture aperture decreases more than micropore diameter during reservoir depletion; (2) with pore pressure decreasing, gas apparent permeability will continue to increase for smaller size microstructures while the apparent permeability will first decrease and then rebound for microstructures with larger size; (3) with pore pressure decreasing, the contribution of slip flow decreases while the significance of Knudsen diffusion increases, and the proportion of surface diffusion first increases and then decreases; (4) with microstructure size increasing, the contribution of slip flow at high pore pressure and the significance of Knudsen diffusion at low pore pressure increase, but the proportion of surface diffusion decreases; (5) gas apparent permeability of micropores is larger than that of microfractures when the cross section area is the same, and the larger aspect ratio leads to smaller microfractures permeability.